México, Guatemala: narrativas sobre violencia contemporánea en textos de Cristina Rivera Garza y Rodrigo Rey Rosa (Altre Modernità, 2019)
The topic discussed by two contemporary Latin-American writers, the Mexican Cristina Rivera Garza and the Guatemalan Rodrigo Rey Rosa, is violence, a recurrent phenomenon in both countries. The genres chosen to express this are: a miscellaneous text with poems, chronicles and essays in Dolerse. Textos desde un pais herido and a novel, a fictional work presented as a historical and autobiographical recount, in El material humano. Rivera Garza believes “writing is a process of production of what is real” and critics present her as an author of “transgressive writing”. Rey Rosa self-exiles from Guatemala for 15 years due to the “violence and social tension” that dominated that country. The author recognizes that his literature at the beginning was abstract, but from 2011 he starts writing about national scenarios with a certain “realistic goal”. The initial purpose of El material humano was an investigation about the fortuitous discovery of millions of documents of the Guatemalan Nacional Police Archive in 2005. The novel also has intertextual reflections, autobiographic information and an enigma to be solved.The historical, political and social violence is transformed into horror, during the war against drugs started in Mexico during Felipe Calderon’s presidency, as well as during the internal war that devastated Guatemala between 1960 and 1996, with the killing of indigenous populations and civilians in urban zones in the 80’s. Both texts show the power of resistance of literature.